2004
DOI: 10.1038/ni1104
|View full text |Cite
|
Sign up to set email alerts
|

PIAS1 selectively inhibits interferon-inducible genes and is important in innate immunity

Abstract: Interferon (IFN) activates the signal transducer and activator of transcription (STAT) pathway to regulate immune responses. The protein inhibitor of activated STAT (PIAS) family has been suggested to negatively regulate STAT signaling. To understand the physiological function of PIAS1, we generated Pias1(-/-) mice. Using PIAS1-deficient cells, we show that PIAS1 selectively regulates a subset of IFN-gamma- or IFN-beta-inducible genes by interfering with the recruitment of STAT1 to the gene promoter. The antiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
209
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 230 publications
(216 citation statements)
references
References 43 publications
6
209
1
Order By: Relevance
“…Herein, we show that CXCL10 induction is regulated at the transcriptional level. Although the CXCL10 gene represents a classical example of a gene that responds to type I/type II IFN-in a STAT1-dependent fashion [24,25], our results show that, in neutrophils, its induction does not reflect a synergistic enhancement of STAT1 activation by IFN-c and LPS. Furthermore, we previously showed that there is no evidence for any IRF-3 or ATF-2/c-Jun involvement regulating CXCL10 mRNA expression in IFN-c plus LPS-treated neutrophils [11], consistent with the data excluding endogenous IFN-b as an intermediate regulating CXCL10 induction.…”
Section: Discussioncontrasting
confidence: 53%
“…Herein, we show that CXCL10 induction is regulated at the transcriptional level. Although the CXCL10 gene represents a classical example of a gene that responds to type I/type II IFN-in a STAT1-dependent fashion [24,25], our results show that, in neutrophils, its induction does not reflect a synergistic enhancement of STAT1 activation by IFN-c and LPS. Furthermore, we previously showed that there is no evidence for any IRF-3 or ATF-2/c-Jun involvement regulating CXCL10 mRNA expression in IFN-c plus LPS-treated neutrophils [11], consistent with the data excluding endogenous IFN-b as an intermediate regulating CXCL10 induction.…”
Section: Discussioncontrasting
confidence: 53%
“…Interestingly, an increased binding of STAT1 to the promoters of PIAS1-sensitive genes, but not PIAS1-insensitive genes, in PIAS1-deficient macrophages was observed [36]. These results suggest that the specificity of PIAS1 on STAT1-mediated gene regulation may be determined, at least in part, by the promoter microenvironment of STAT1-target genes.…”
Section: Pias In the Regulation Of Stat Signalingmentioning
confidence: 80%
“…Pias1 -/-mice are produced at a frequency 50% lower than the expected Mendelian ratio due to partial perinatal lethality. The surviving PIAS1-deficient mice are runted compared with their wild-type littermates [36]. Wild type and Pias1 -/-bone-marrow-derived macrophages (BMDMs) and primary mouse embryonic fibroblasts (MEFs) have been used to analyze the physiological role of PIAS1 in STAT1 signaling [36].…”
Section: Pias In the Regulation Of Stat Signalingmentioning
confidence: 99%
See 2 more Smart Citations